In-vitro evaluation of antifungal potential of some fungal bio-agents against different Alternaria species - Pahnwar, Safia; Lodhi, Abdul Mubeen; Nizamani, Imtiaz Ahmed; Khaskheli, Asad Ali; Khaskheli, Allah Jurio; Poussio, Gul Bahar; Khaskheli, Sajad Ali; Khaskheli, Muhamad Ibrahim (Journal of Pure and Applied Agriculture, 2023)
Biological control is always being encouraged to manage several plant pathogens for eco-friendly management. The aim of the current manuscript was to evaluate antifungal potential of some fungal bio-agents (BCAs) against different Alternaria species (Alternaria tenuissima, Alternaria solani and Alternaria alternata) isolated from major Kharif vegetables viz chilli, tomato and eggplant, respectively. The in-vitro antifungal potential of different BCAs revealed significantly (P < 0.05 = 0.0000) highest efficacy percent over control against A. solani of tomato fruit rot with T. viride (54.99%) followed by Paecilomyces sp. (53.33%), T. hamatum (44.98%) and T. harzianum (31.12%), whereas the lowest efficacy percent was observed with Penicillium sp. (3.37%) when tested with a dual culture methods. In a volatile method, significantly highest efficacy percent was noticed wit